Tischner - życie w opowieściach. Cz. 1-2 scen. Witold Bereś, Artur Więcek "Baron" ; reż. Artur Więcek. - Bereś, Witold (1960- ).; Więcek, Artur (1967- ).; Trela, Piotr (1967- ).; Pawluśkiewicz, Jan Kanty (1942- ).; Tischner, Barbara (1940-2022); Tischner, Janina; Tischner, Joanna (Kolekcja Tygodnika Powszechnego, 2008)
Biografia oparta na wspomnieniach rodziny ks. Tischnera.